2016
DOI: 10.1016/j.ygyno.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy and primary debulking surgery utilization for advanced-stage ovarian cancer at a comprehensive cancer center

Abstract: Objective The aim of this study was to evaluate the use of neoadjuvant chemotherapy (NACT) and primary debulking surgery (PDS) before and after results from a randomized trial were published and showed non-inferiority between NACT and PDS in the management of advanced-stage ovarian carcinoma. Methods We evaluated consecutive patients with advanced-stage ovarian cancer treated at our institution from 1/1/08–5/1/13, which encompassed 32 months before and 32 months after the randomized trial results were publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 29 publications
5
86
2
1
Order By: Relevance
“…There has been an increase in use of neoadjuvant chemotherapy in North America over the last few years. 5,22,24 This trend is likely the consequence of 2 recent randomized controlled trials reporting equivalent survival rates among women with advanced ovarian carcinoma that were treated with neoadjuvant chemotherapy or primary debulking surgery. 11,12 The results from the current study question this position.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increase in use of neoadjuvant chemotherapy in North America over the last few years. 5,22,24 This trend is likely the consequence of 2 recent randomized controlled trials reporting equivalent survival rates among women with advanced ovarian carcinoma that were treated with neoadjuvant chemotherapy or primary debulking surgery. 11,12 The results from the current study question this position.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, NAC followed by an IDS was limited to patients who were poor surgical candidates or unlikely to be resected optimally [7, 9-12, 14-22, 25-29, 31-40]. However, the EORTC/NCIC trial showed the similar median OS (30.0 vs. 29.0 months) and median PFS (12 vs. 12 months) between the NAC group and PDS group, concluding that NAC followed by IDS was a reasonable treatment for advanced ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The role of first-line surgery in advanced OC is upheld by international guidelines (61, 62) on the basis of data from existing studies, which are mainly retrospective, and from single series of prospective studies, as well as systematic reviews (63)(64)(65)(66)(67)(68)(69)(70). It should be carried out by an oncologic gynecologist (71).…”
Section: Topic 4: Peritonectomy: Total or Locoregional?mentioning
confidence: 99%